The Causal Effect of Cultural Identity on Cooperation - Jeffrey V. Butler; Dietmar Fehr (Center for Economic Studies and Ifo Institute (CESifo), 2021)
The impact of culture on non-kin cooperation has been singled out as critical for economic activity. However, causal evidence of culture's influence on cooperation remains scant. In this paper we provide such evidence, focusing on two key components of culture: preferences and beliefs. Adopting the view that culture is one aspect of an individual's multi-faceted self-concept (identity) we conduct an experiment with foreign- and US-born Chinese immigrants at a large US public university. In a two-by-two design, we exogenously vary: i) the salience of participants' American or Chinese cultural identities; and ii) the capacity for culture to affect beliefs by randomly providing previous-session cooperation-rate information. Comparing behavior across cultures and information conditions, our results suggest a prominent role for both preferences and beliefs. In particular, we find that culture's effects through beliefs are as important as its effects through preferences.
Keywords: C91; D01; O10; P16; Z10; 330; culture; identity; beliefs; preference; experiment